2018
DOI: 10.1002/ccd.27808
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transcatheter patent ductus arteriosus closure in extremely low birth weight infants

Abstract: Background Patent ductus arteriosus (PDA) is common in extremely low birth weight (ELBW) infants. The objectives of this study were to describe our early clinical experience of transcatheter PDA closure (TCPC) in ELBW infants, compare outcomes with surgical ligation of PDA (SLP), and identify risk factors for prolonged respiratory support. Methods A retrospective review was performed comparing infants born <27 weeks, weighing <1 kg at birth and < 2 kg during TCPC with 2:1 propensity‐score matched group of infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 30 publications
2
91
0
Order By: Relevance
“…In the most recent years, several cohort studies reported preliminary experience with transcatheter technique, using various devices for PDA closure in premature infants (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). Comparison with surgical ligation revealed a positive impact on post procedure pulmonary outcome (49,50). The procedure has been well-described in preterm infants, including extremely low birth weight (ELBW) infants as small as 640 g (50).…”
Section: Transcatheter Closure Of Pda In Extremely Preterm Infants: Bmentioning
confidence: 99%
See 1 more Smart Citation
“…In the most recent years, several cohort studies reported preliminary experience with transcatheter technique, using various devices for PDA closure in premature infants (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). Comparison with surgical ligation revealed a positive impact on post procedure pulmonary outcome (49,50). The procedure has been well-described in preterm infants, including extremely low birth weight (ELBW) infants as small as 640 g (50).…”
Section: Transcatheter Closure Of Pda In Extremely Preterm Infants: Bmentioning
confidence: 99%
“…Comparison with surgical ligation revealed a positive impact on post procedure pulmonary outcome (49,50). The procedure has been well-described in preterm infants, including extremely low birth weight (ELBW) infants as small as 640 g (50). Following the results of an ongoing prospective trial using the ADO II AS, this device received FDA and CE approval for transcatheter closure of PDA in premature babies weighting more than 700 g and over 3 days old (51).…”
Section: Transcatheter Closure Of Pda In Extremely Preterm Infants: Bmentioning
confidence: 99%
“…Optimal imaging is paramount while performing TCPC. Since TCPC involves no direct visualization of the PDA, the operator is dependent on fluoroscopic and echocardiographic imaging . All this equipment occupies a large space.…”
Section: Discussionmentioning
confidence: 99%
“…TCPC is a relatively new technique that is constantly being refined for the purpose of performing this procedure safely in ELBW infants. Among the many advantages of TCPC over medical therapy is that it guarantees definitive closure of the PDA with limited risks (as low as 3% in some reports in ELBW infants) . Since, no “cutting and stitching” of the baby is required unlike surgical ligation, it can prevent complications associated with thoracotomy including post‐ligation syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Among the many advantages of TCPC over medical therapy is that it guarantees definitive closure of the PDA with limited risks (as low as 3% in some reports in ELBW infants) . Since, no “cutting and stitching” of the baby is required unlike surgical ligation, it can prevent complications associated with thoracotomy including post‐ligation syndrome . Since this is a new therapy, awareness among neonatologists regarding the feasibility and safety of this technique is still lacking.…”
Section: Discussionmentioning
confidence: 99%